Laju Infiltrasi Air di Lubang Biopori pada Berbagai Jenis Tanah di Kelurahan Loa Bakung - Arrosyidah, Mosy R; Djayus, Djayus; Mislan, Mislan; Munir, Rahmiati (GEOSAINS KUTAI BASIN, 2024)
The reduction of green open space results in a lack of infiltration of rainwater into the soil and an increase in the amount of surface flow, one solution to overcome these problems is to implement a biopore infiltration hole system. This study aims to determine the rate and capacity of water infiltration in biopore holes based on various soil types in Loa Bakung Village. The infiltration rate was determined through direct measurement at 9 points in 3 locations with gleisol, podzolic, and podzolic haplik soil types, then measured by putting water into a hole with a diameter of 10 cm with a depth of 80 cm - 100 cm. The parameters measured are the difference in distance or height and time. The results of parameter measurements were made into a graph to obtain the highest infiltration rate at the research location, and determine the infiltration capacity using the Horton equation. Then, soil samples were analyzed by measuring soil physical properties that affect infiltration rates such as texture, porosity, permeability, and moisture content. The results showed that the infiltration rate and infiltration capacity varied in each location. Location 2 with podzolic soil type shows the highest infiltration rate and capacity value of 2820 cm/hour with an infiltration capacity of 2782.84 cm/hour. Followed by location 1 which is a gleisol soil type of 1224 cm/hour with an infiltration capacity of 1217.72 cm/hour, and the lowest value is shown in location 3 with a haplik podzolic soil type of 1050 cm/hour with an infiltration capacity of 1041.46 cm/hour.